Capital Structure And Corporate Financial Performance: Evidence From Nigerian Cement Companies - Ogbulu, M. O.; Okanta, Sunday Ukeje; Turakpe, Morrison J. (Archives of Business Research, 2018)
This study seeks to examine the impact of capital structure on corporate financial performance of four cement companies in Nigeria for the period 2006 – 2015. Data selected as proxies for the financial performance of the firms, which included return on asset (ROA), return on equity (ROE), and return on sales (ROS) were generated from the firm’s audited annual financial reports. Data on total debt/asset ratio (TDA), long-term debt/asset ratio (LDA), and equity/asset ratio (EQA) were selected as proxies for capital structure of the firms. Also, data on asset-turnover ratio (ATO) (measurement for asset utilization), total asset (TAST) and total sale (TSAL) – measurements for firm size, were selected as control variables. The parameters of the above variables were estimated using Autoregressive Distributed Lag (ARDL) method. The result of the study revealed that all the capital structure variables (TAD, LDA and EQA) have mixed impact on financial performance indicators (ROA, ROE and ROS) used in the study. While there existed positive relationships between the control variables of ATO, TAST and performance, TSAL negatively related to financial performance measures. Following from the findings of the study, corporate decision makers in Nigerian cement industry should be careful in the use of debts. While it is necessary to use debt as a source of finance, such a decision should be a last option as supported by the Pecking order theory. Rather, retained earnings should be preferred.